Analisis Rasio Keuangan Terhadap Perubahan Laba (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Makanan dan Minuman yang Terdaftar di BEI Tahun 2017-2019) - Muh Kusnan Hamid; Subadriyah Subadriyah (Jurnal Rekognisi Akuntansi, 2021)
This study aims to analyze financial ratios to changes in earnings. The rapid development of the capital market creates various opportunities or alternatives for investors. On the other hand, companies seeking funds must compete in getting funds from investors. One way for companies to raise funds is by issuing and selling their shares to investors in the stock market. In line with the formulation of the problem, the purpose of this paper is as follows to provide empirical evidence about the effect of changes in Total Asset Turnover, Deb to Equity Ratio, Net Profit Margin and Current Ratio. To predict changes in earnings in manufacturing companies for the next one year period. The target population of this study are manufacturing companies in the food and beverage industry listed on the Indonesia Stock Exchange from 2017 to 2019, with purposive sampling technique, a research sample of 34 companies in the consumer goods sector was obtained. The results of this study indicate that the Total Asset Turnover, Debt to Equity Ratio, and Curret Ratio variables do not have a major effect on changes in earnings.